Optoelectronic properties of benzotrithiophene isomers: A density functional theory study. Issue 8 (3rd March 2019) - Tripathi, Anuj; Chetti, Prabhakar
Abstract : Benzotrithiophene (BTT) isomers were investigated using density functional theory (DFT) and time‐dependent DFT (TD‐DFT) with the aim to explore their structures, linear optical properties, vertical and adiabatic ionization potentials ( IP v and IP a ), electron affinities ( EA v and EA a ), and reorganization energies ( λ ). The computed bond lengths and bond angles at the B3LYP/6–311+G (d, p) level of theory are in good agreement with experimental crystal structures of the known BTTs. These molecules are planar with zero dihedral angle, making them an ideal backbone for high charge mobility. The UV–visible spectra of BTT isomers are in the range 280–360 nm. All BTT isomers have low hole/electron reorganization energies, which is the main characteristic of good hole/electron transporting materials, and these isomers in turn have potential applications in the field of organic materials. Abstract : Linear optical properties and reorganization energies of Benzotrithiophene (BTT) isomers have been studied. It is observed from calculated reorganization energies that these are ambipolar in nature and are suitable for applications in organic electronic materials. All the BTT isomers having low hole/electron reorganization energies indicate they can be used as better hole/electron transporting materials.